2021
DOI: 10.1371/journal.pone.0254726
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for severe neutropenia in pancreatic cancer patients treated with gemcitabine/nab-paclitaxel combination therapy

Abstract: Aim Combination therapy with gemcitabine and nanoparticle albumin-bound paclitaxel (nab-paclitaxel), known as GnP therapy, significantly prolongs the survival of pancreatic cancer patients compared with gemcitabine monotherapy. However, it may cause severe neutropenia, requiring discontinuation of treatment. This study aimed to clarify the risk factors for Grade 3/4 neutropenia during GnP therapy. Methods Clinical data of pancreatic cancer patients who underwent GnP therapy at the Cancer Institute Hospital o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…28 Decreased ANC has also been reported as an informative risk predictive factor in a variety of chemotherapy regimens. 29 Although some studies have shown that BMI could be used as a predictive factor, 30,31 it was not included in the final model in our study. One possible reason may be that the dose received by patients was calculated based on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…28 Decreased ANC has also been reported as an informative risk predictive factor in a variety of chemotherapy regimens. 29 Although some studies have shown that BMI could be used as a predictive factor, 30,31 it was not included in the final model in our study. One possible reason may be that the dose received by patients was calculated based on BMI.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence rate of EOSN increased as the number of risk factors increased. Risk factors for severe neutropenia have been investigated in several malignancies, including gastrointestinal cancer, the identified factors partly depend on the cancer types and regimens (14)(15)(16)(17)(18)(19).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it was unclear whether all risk factors were extracted. This study did not include hemoglobin, total bilirubin, or creatinine clearance, which were reported as risk factors in other studies ( 15 - 17 , 19 ). Further studies with larger sample sizes are required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In cancer, the pro‐tumor and antitumor effects of neutrophils remain inconclusive 72 . Gemcitabine monotherapy, as well as its combination with other chemotherapies, may induce levels of neutropenia (and thrombocytopenia) that can be of clinical concern 73–75 . Surprisingly, incidence of chemotherapy‐induced neutropenia (CIN) has been correlated with improved survival in cancer patients, 76 and for gemcitabine‐treated pancreatic cancer patients, early‐onset CIN was identified as a predictor of more favorable prognosis 77 …”
Section: Immunomodulatory Effects Of Gemcitabine On Immune Cellsmentioning
confidence: 99%